A Simple Paper Based Microfluidic Electrochemical Biosensor for Point‐of‐Care Cholesterol Diagnostics. Issue 12 (9th November 2017) - Kaur, Gurpreet; Tomar, Monika; Gupta, Vinay
Abstract : Paper based microfluidic devices have emerged as a simple and low cost platform for efficient clinical diagnostics. An effort has been made in the present work to develop a microfluidic cholesterol biosensor using paper based platform. Microfluidic channels have been fabricated by patterning filter paper (Whatman 1) using photolithography. SU 8 photoresist formed a hydrophobic barrier on the paper with microchannels of dimensions 1000 μm(w)×100 μm(t). A three electrode system was fabricated by simple mask printing of graphite as the working, as well as the counter electrodes, and silver as the reference electrode. The working electrode was modified using nickel oxide nanoparticles prepared using co‐precipitation method. Cholesterol oxidase enzyme is spotted on the test zone and chronoamperometric measurements are taken for different concentrations of cholesterol in the range of 0.12–10.23 mM, giving a quick and sensitive detection with a sensitivity of 24 µA mM −1  cm −2 . Abstract : Microfluidic paper based biosensor has been fabricated by patterning filter paper (Whatman 1) using SU 8 photolithography. One circular end of the paper is the analyte zone and the other end is the detection zone. A three electrode system was fabricated over the detection zone by simple mask printing for amperometric detection of cholesterol.